Inhibition of DNA methylation promotes breast tumor sensitivity to netrin‐1 interference. Issue 8 (4th July 2016) - Grandin, Mélodie; Mathot, Pauline; Devailly, Guillaume; Bidet, Yannick; Ghantous, Akram; Favrot, Clementine; Gibert, Benjamin; Gadot, Nicolas; Puisieux, Isabelle; Herceg, Zdenko; Delcros, Jean‐Guy; Bernet, Agnès; et al.
Abstract: In a number of human cancers, NTN1 upregulation inhibits apoptosis induced by its so‐called dependence receptors DCC and UNC5H, thus promoting tumor progression. In other cancers however, the selective inhibition of this dependence receptor death pathway relies on the silencing of pro‐apoptotic effector proteins. We show here that a substantial fraction of human breast tumors exhibits simultaneous DNA methylation‐dependent loss of expression of NTN1 and of DAPK1, a serine threonine kinase known to transduce the netrin‐1 dependence receptor pro‐apoptotic pathway. The inhibition of DNA methylation by drugs such as decitabine restores the expression of both NTN1 and DAPK1 in netrin‐1‐low cancer cells. Furthermore, a combination of decitabine with NTN1 silencing strategies or with an anti‐netrin‐1 neutralizing antibody potentiates tumor cell death and efficiently blocks tumor growth in different animal models. Thus, combining DNA methylation inhibitors with netrin‐1 neutralizing agents may be a valuable strategy for combating cancer. Synopsis: Inhibition of DNA methylation with decitabine restores expression of netrin‐1 (NTN1) and DAPK1 in human breast tumors. Combining decitabine with NTN1 neutralization potentiates tumor cell death and blocks tumor growth in various animal models. NTN1 and DAPK1 are frequently hypermethylated and lost in human breast cancers. NTN1 and DAPK1 loss of expression is associated with a loss of apoptosis induction upon netrin‐1 targeting antibody treatment. Epigenetic drugs such as decitabine (DAC) induce demethylation and upregulation of DAPK1 and NTN1 in tumor cells, thus leading to cell resensitization to netrin‐1 targeting antibodies. Combinatorial DAC + net1‐mAb treatment triggers cell death in vitro and tumor growth inhibition in mice. Abstract : Inhibition of DNA methylation with decitabine restores expression of netrin‐1 (NTN1) and DAPK1 in human breast tumors. Combining decitabine with NTN1 neutralization potentiates tumor cell death and blocks tumor growth in various animal models.